Bacteriophage-Resistant Mutant of Enterococcus faecalis Is Impaired in Biofilm Formation - Liu, Jiazhen; Zhu, Yanpeng; Li, Yang; Lu, Yuwen; Xiong, Kun; Zhong, Qiu; Wang, Jing (Frontiers in Microbiology, 2022)
Enterococcus faecalis (E. faecalis) is a common gram-positive non-spore-forming bacterium in nature and is resident in the upper respiratory tract, intestine, and mouth of healthy people. Moreover, E. faecalis is also one of the common pathogens causing nosocomial infections and is resistant to several antibiotics commonly used in the clinic. Thus, it is difficult to treat drug-resistant E. faecalis with antibiotics and new approaches to treat E. faecalis infection are needed. In this study, we isolated a bacteriophage named EFap02 from the Southwest hospital swage that targets E. faecalis strain EFa02. Phage EFap02 belongs to the Siphoviridae family, and its receptor was identified as capsular polysaccharides, Phage-resistant mutant had loss-of-function mutations in glycosyltransferase (gtr2) responsible for capsular polysaccharide biosynthesis, which caused the capsular polysaccharide loss and interruption of phage adsorption. Though phage-resistant mutant against EFap02 could be selected, the mutant is impaired in biofilm formation due to the loss of capsular polysaccharides. Thus, this study provided a detailed description of E. feacalis phage EFap02 with the potential for treating E. faecalis infection.